The Effect of Kahoot on Learning Performance of Prospective Elementary School Teacher in Indonesia - Salam, Ibnu; Kurniawati, Wahyu; Izhar, Gusti (FKIP Universitas Lampung, 2022)
Effect of Kahoot Media on Learning Outcomes of Prospective Elementary School Teacher Students. Objectives: This study aims to determine the effect of Media Kahoot on the learning outcomes of PGSD students. Methods: This research is a quasi-experimental research, namely by applying the use of Kahoot Media in the experimental class, the treatment is carried out to examine student learning performance. Findings: The average post-test score for the experimental class using Kahoot Media was 87.24 while the average in the Control class was 79.35. So that there is an increase in the average value of 7.89 using Kahoot Media. The use of Kahoot Media on the material characteristics of living things is quite effective for student learning outcomes. Conclusion: It is expected that lecturers and students use Kahoot Media as one of the interesting and interactive supporting media at the school and college level. Keywords: kahoot media, learning outcomes students, elementary school teacher students.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202205